Untargeted metabolite profiling to elucidate rhizosphere and leaf metabolome changes of wheat cultivars (Triticum aestivum L.) treated with the plant growth-promoting rhizobacteria Paenibacillus alvei (T22) and Bacillus subtilis - Mashabela, Manamele D.; Tugizimana, Fidele; Steenkamp, Paul A.; Piater, Lizelle A.; Dubery, Ian A.; Mhlongo, Msizi I. (Frontiers in Microbiology, 2022)
The rhizosphere is a highly complex and biochemically diverse environment that facilitates plant-microbe and microbe-microbe interactions, and this region is found between plant roots and the bulk soil. Several studies have reported plant root exudation and metabolite secretion by rhizosphere-inhabiting microbes, suggesting that these metabolites play a vital role in plant-microbe interactions. However, the biochemical constellation of the rhizosphere soil is yet to be fully elucidated and thus remains extremely elusive. In this regard, the effects of plant growth-promoting rhizobacteria (PGPR)-plant interactions on the rhizosphere chemistry and above ground tissues are not fully understood. The current study applies an untargeted metabolomics approach to profile the rhizosphere exo-metabolome of wheat cultivars generated from seed inoculated (bio-primed) with Bacillus subtilis and Paenibacillus alvei (T22) strains and to elucidate the effects of PGPR treatment on the metabolism of above-ground tissues. Chemometrics and molecular networking tools were used to process, mine and interpret the acquired mass spectrometry (MS) data. Global metabolome profiling of the rhizosphere soil of PGPR-bio-primed plants revealed differential accumulation of compounds from several classes of metabolites including phenylpropanoids, organic acids, lipids, organoheterocyclic compounds and benzenoids. Of these, some have been reported to function in plant-microbe interactions, chemotaxis, biocontrol and plant growth promotion. Metabolic perturbations associated with the primary and secondary metabolism were observed from the profiled leaf tissue of PGPR-bio-primed plants, suggesting a distal metabolic reprogramming induced by PGPR seed bio-priming. These observations gave insights into the hypothetical framework which suggests that PGPR seed bio-priming can induce metabolic changes in plants leading to induced systemic response for adaptation to biotic and abiotic stress. Thus, this study contributes knowledge to ongoing efforts to decipher the rhizosphere metabolome and mechanistic nature of biochemical plant-microbe interactions, which could lead to metabolome engineering strategies for improved plant growth, priming for defence and sustainable agriculture.